2018
DOI: 10.1002/mc.22938
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin‐β receptor‐NIK signaling induces alternative RELB/NF‐κB2 activation to promote metastatic gene expression and cell migration in head and neck cancer

Abstract: Head and neck squamous cell carcinomas (HNSCC) preferentially spread to regional cervical tissues and lymph nodes. Here, we hypothesized that lymphotoxin‐β (LTβ), receptor LTβR, and NF‐κB‐inducing kinase (NIK), promote the aberrant activation of alternative NF‐κB2/RELB pathway and genes, that enhance migration and invasion of HNSCC. Genomic and expression alterations of the alternative NF‐kB pathway were examined in 279 HNSCC tumors from The Cancer Genome Atlas (TCGA) and a panel of HNSCC lines. LTβR is amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Despite several advances in the management of OPSCC including novel imaging as well as innovations in surgical and radiotherapeutic techniques, the overall survival of patients with OPSCC still remains around 50% at 5 years, primarily because of locoregional and/or systemic recurrence of disease [ 2 ]. In recent years, many efforts have been undertaken to identify novel molecular and cellular prognostic biomarkers in order to improve the prediction of the risk of OPSCC recurrence, however, high costs of analyses, time-consuming preparation and lack of standardization limit their application in routine clinical practice [ 3 ]. In addition, there is increasing data demonstrating that radiomics provides important prognostic information for the risk assessment of specific outcomes in head and neck cancer [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite several advances in the management of OPSCC including novel imaging as well as innovations in surgical and radiotherapeutic techniques, the overall survival of patients with OPSCC still remains around 50% at 5 years, primarily because of locoregional and/or systemic recurrence of disease [ 2 ]. In recent years, many efforts have been undertaken to identify novel molecular and cellular prognostic biomarkers in order to improve the prediction of the risk of OPSCC recurrence, however, high costs of analyses, time-consuming preparation and lack of standardization limit their application in routine clinical practice [ 3 ]. In addition, there is increasing data demonstrating that radiomics provides important prognostic information for the risk assessment of specific outcomes in head and neck cancer [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genes involved in the alternative NF-κB pathway such as BIRC3 were highly inducible by LTβ in a HPV(+) cell line. The latter findings might guide future targeted and immune therapies in HPV(+) HNSCC, where inhibition of the alternative NF-κB pathway or prosurvival targets such as BIRC3 (IAP2) combined with activation of the death pathway by death receptor agonists could be more effective (12,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The classical pathway plays an important role in cancer cell proliferation and survival, and in therapeutic resistance (4)(5)(6)(7). In HNSCC, we also showed that components of the alternative NF-κB pathway, RELB and NF-κB2 (p100/p52), are modulated by lymphotoxin-β (LTβ) and other ligands through the activation of NF-κB inducing kinase (NIK) and IKKα (CHUK) (11,12). The alternative pathway promotes tumor cell migration, an important feature underlying malignant spread and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies from our lab demonstrated that key components of the canonical NFκB pathway are aberrantly activated in HNSCC and are further activated by TNFα via the IKK complex [ 22 , 102 , 103 ]. Furthermore, recent studies have demonstrated the activation of non-canonical NFκB signalling, involving NIK and IKKα [ 104 , 105 , 106 ]. Both of the NFκB pathways have also been shown to interact with other pro-oncogenic signalling pathways, including the EGFR, STAT3, and AP-1 pathways [ 104 , 107 , 108 ].…”
Section: Ubiquitin-mediated Nfκb Signalling In Head and Neck Squammentioning
confidence: 99%